Design and analysis of active disturbance rejection and field weakening control system for PMSM based on FCS-MPC - YU Yuting; HUANG Jie; CHU Yanting; ZHOU Fangyuan (机车电传动)
The field weakening control system for permanent magnet synchronous motors (PMSM) is commonly used in the field of electric vehicles (EV). PMSMs need to deliver high torque output to meet the demands of rapid starting, acceleration, and climbing for EVs when operating at low speeds. Moreover, they needs to maintain a certain load capacity in a field weakening state to support high-speed driving and overtaking for EVs when operating beyond the rated speed. To address speed mutations in PMSM field weakening control, this paper proposes the design of an active disturbance rejection controller (ADRC) to replace the proportional integral (PI) controller in the speed outer loop. The ADRC can quickly observe and compensate for disturbance terms, reducing system interference caused by speed mutations and enabling accurate speed tracking. To mitigate torque term interferences, this paper presents a combination of finite control set model predictive control (FCS-MPC) and a model predictive torque control system based on torque and flux linkage output design, to replace traditional direct torque control (DTC). Based on a value function constructed to minimize torque and flux linkage ripples, calculations and optimizations enable the selection of optimal space vector control signals that are then transmitted to the inverters. The optimized field weakening control system, incorporating both ADRC and FCS-MPC, demonstrates improvements in disturbance immunity, as well as current and torque output torque. The feasibility and performance advantages of the designed system are verified through experiments.